2013
DOI: 10.1371/journal.pone.0053525
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Association Study Identifies Genomic Regions for Virulence in the Non-Model Organism Heterobasidion annosum s.s

Abstract: The dense single nucleotide polymorphisms (SNP) panels needed for genome wide association (GWA) studies have hitherto been expensive to establish and use on non-model organisms. To overcome this, we used a next generation sequencing approach to both establish SNPs and to determine genotypes. We conducted a GWA study on a fungal species, analysing the virulence of Heterobasidion annosum s.s., a necrotrophic pathogen, on its hosts Picea abies and Pinus sylvestris. From a set of 33,018 single nucleotide polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 50 publications
0
60
0
Order By: Relevance
“…For example, because of the importance of pathogenic fungi to human and plant health, fungal genomes are being characterized to identify virulence effectors and other sequences associated with pathogenesis (96)(97)(98)(99). However, infection of pathogenically diverse fungal isolates with virulencealtering mycoviruses could reduce the abilities of such studies to identify chromosomal regions linked to disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, because of the importance of pathogenic fungi to human and plant health, fungal genomes are being characterized to identify virulence effectors and other sequences associated with pathogenesis (96)(97)(98)(99). However, infection of pathogenically diverse fungal isolates with virulencealtering mycoviruses could reduce the abilities of such studies to identify chromosomal regions linked to disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…& Otrosina in contrast to nonpathogenic basidiomycetes. Besides, H. annosum s.s. genom studies showed that genes coded proteins responsible for virulence factor are also connected with iron metabolism (Dalman et al 2013). Oxalic acid has also been reported to play a role in the pathogenicity of Sclerotinia sclerotiorum (Lib.)…”
Section: Discussionmentioning
confidence: 99%
“…& Otrosina in contrast to other nonpathogenic basidiomycetes. The regions essential in virulence of H. annosum s.s. coded proteins involved in iron metabolism (Dalman et al 2013). Our previous studies showed that iron together with H 2 O 2 is involved in cell death of P. sylvestris challenged by H. annosum s.s. .…”
Section: Introductionmentioning
confidence: 99%
“…Recent work with other chronic granulomatous diseases, most notably tuberculosis, has led to the recognition of a subset of pathogenic strains that cause more serious infections due to enhanced expression of virulence determinants [57]. Similar genome-wide association studies (GWAS) in other fungi including pathogens have revealed important understanding of virulence mechanisms [58][59][60]. GWAS is a promising approach to understand genetic basis of disease severity in Coccidioides strains.…”
Section: How Relevant Are Current Guidelines About When and How To Trmentioning
confidence: 99%